Influence of medical and social factors on parents' attitude to specific prevention of infectious diseases in children of the Saratov region during the new coronavirus infection pandemic - E. V. Mikhailova; T. N. Malugina; D. Yu. Levin; A. N. Polyakova; A. Yu. Serdyukov (Детские инфекции (Москва))
Objective: to analyze the influence of medical and social factors on the attitude of parents to the specific prevention of infectious diseases in children during the pandemic of a new coronavirus infection. Material and methods. Anonymous questioning of parents on the attitude to vaccination was conducted. A specially designed questionnaire included questions about attitudes towards vaccines included in the National Immunization Schedule, as well as those not included in it, in particular, the desire of parents to vaccinate their children against COVID-19 was assessed. In total, 153 people aged 17 to 42 took part in the survey — parents of children aged 1 to 14 years. Results. All parents under 18 years of age support vaccination in accordance with the National Vaccination Calendar; 52.1% of parents aged 18—25 years (p < 0.001), 55.6% of parents aged 26—35 years (p < 0.001 compared to parents under 18 years old), and 66.7% of parents over 35 years old (p < 0.001 compared to parents under 18 years old and parents 18—35 years old). Conclusion. The main medical and social factors associated with the refusal to carry out preventive vaccinations for their children are: the age of parents under 35, incomplete higher education and trust in information received on the Internet. The results obtained indicate the need to determine the «risk group» among parents who express doubts about the need for vaccination. It is necessary to conduct educational programs for them in order to form a positive attitude towards the specific prevention of infectious diseases.